Digital Transformation of MSMEs: Navigating Opportunities and Challenges in the Industry 4.0 Era - Lapian, Stanss. L. H. V. Joyce; Mandey, Silvya L.; Tumbuan , Willem J. F. A.; Ogi, Imelda W. J.; Suripatty, Roberthair; Winarsih; Makalisang, Meiland; Ormak, Naomi (Public Policy, 2025)
This study examines the opportunities and challenges encountered by Micro, Small, and Medium Enterprises (MSMEs) in adopting digital technologies within the framework of the Fourth Industrial Revolution. Digital platforms present numerous benefits, including enhanced operational efficiency, expanded market reach, and increased potential for innovation. Nevertheless, MSMEs face several obstacles, such as inadequate infrastructure, limited digital skills, financial constraints, and concerns related to cybersecurity. To mitigate these challenges, the study recommends continuous digital training, infrastructure development, improved access to financing, and comprehensive cybersecurity awareness programs. These strategic initiatives are intended to support MSMEs in effectively navigating digital transformation, enhancing their competitiveness, and achieving long-term sustainability in the global digital economy.